Hubungan Stres dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Sei Pancur Kota Batam Tahun 2018 - Asfri Sri Rahmadeni; Lela Fajar; Nahrul Hayat (Jurnal Sehat Mandiri, 2019)
Hypertension is a condition in which blood pressure increases persistently which is ranked number one cause of death each year. It is estimated that in 2025 there will be 1.5 billion people suffering from hypertension, this problem occurs in many developed and developing countries. The purpose of this study was to determine the relationship of stress with the incidence of hypertension at the Sei Pancur Health Center in Batam City in 2018. The research method used analytical design with a cross sectional design. The sampling technique of this study used non-probability sampling technique with purposive sampling totaling 61 samples. The results of this study found that the stress experienced was in very heavy stress the majority of 62.3% of respondents, the majority of 91.8% of respondents experienced hypertension. The results of the analysis there is a relationship between stress and the incidence of hypertension with a value of ρ = 0.001 <0.05. Based on this, it is recommended that health services improve health care problems, especially problems that cause hypertension.